Engagement of Undergraduate Students as Custodians in Heritage Conservation Enrichment - Pue Giok Hun, (Kajian Malaysia, 2017)
In 2005, National Heritage Act was enacted by the Government of Malaysia as an effort to protect and preserve tangible and intangible cultural heritage in the country. Despite its significance and well intentions, the Act remains weak and limited in terms of its definition, scope, implementation and awareness. This, in particular, becomes problematic when it comes to intangible cultural heritage (ICH) as it is living and continuously evolving. The increasingly rapid globalisation at the end of the 20th century causes more communities to become susceptible to frequent changes. In addition, Malaysian studies itself is still in the early phase of forming and building the breadth and depth of local knowledge of the country and its society. One particular aspect of concern is knowledge about minority ethnic groups with the potentials to be considered as regional heritage such as the various Peranakan communities in Malaysia. Hence, it is a race against time to have the communities' rich and invaluable culture documented for future preservation and conservation. Against this background, the present article explores theses as a potential viable source of knowledge on a minority ethnic community in Malaysia with a focus on Peranakan Chinese in Kelantan. Selected available theses pertaining to social aspects of the community that were written at bachelor degree levels at Universiti Kebangsaan Malaysia (UKM) and Universiti Malaya (UM) from 1970s to 2010s are analysed using content analysis technique. Findings of the study suggests that theses can potentially serve as custodians to the untapped "treasure trove" of Malaysian heritage by preserving arcane information of the community at the grass-root level. Several theses written even go beyond "potentials" after they were polished and published as books, subsequently providing a significant contribution to building and defining what we now know about the community and its heritage.